2021
DOI: 10.1111/tct.13336
|View full text |Cite
|
Sign up to set email alerts
|

Improv to improve medical student communication

Abstract: Patient-centred communication (PCC), including empathetic communication (EC), has well described health benefits to patients. 1 Various educational interventions, many with lengthy time commitments, attempting to improve PCC, EC and patient satisfaction survey scores (PSSS) have had mixed results. 2 Improvisational theatre ('improv') is emerging as an instructional strategy for teaching communication skills. 3 The fundamental skills of improv parallel the skills that Epstein et al advocates for PCC. 4 Improv r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…In the definition sections, seven studies mentioned cognitive dimensions of empathy, nine mentioned affective dimensions of empathy, and six mentioned behavioral dimensions of empathy. On the other hand, four studies did not define empathy in any dimension [ 27 , 34 , 40 , 48 ], while one study defined empathy in one dimension, three studies in two dimensions, and only five studies in all three dimensions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the definition sections, seven studies mentioned cognitive dimensions of empathy, nine mentioned affective dimensions of empathy, and six mentioned behavioral dimensions of empathy. On the other hand, four studies did not define empathy in any dimension [ 27 , 34 , 40 , 48 ], while one study defined empathy in one dimension, three studies in two dimensions, and only five studies in all three dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…The other three studies were 33% consistent [ 18 , 37 , 42 ], which involved the behavioral dimension only. The remaining studies had either no consistency at all, found in eight studies [ 21 , 23 , 27 , 38 , 40 , 44 , 45 , 48 ], or inapplicability for comparison, found in one study [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations